Who turns the global thermostat and by how much? - Wilfried Rickels; Martin F. Quaas; Katharine Ricke; Johannes Quaas; Juan Moreno-Cruz; Sjak Smulders (Energy Economics, 2020)
Increasing attention is being given to the option of engineering the climate via Solar Radiation Management (SRM) as a potential component in future climate policies. We set up a quantitative model to analyze efficient levels of SRM deployment against the climatic and economic background conditions projected by the various Shared Socioeconomic Pathways (SSPs) baseline scenarios for the year 2050. The model combines three features of the data: i) SRM deployment is regionally uneven in the way it affects grid-cell temperature and precipitation, ii) temperature and precipitation affect Gross Value Added (GVA) at the grid-cell level and the effect for both takes the form of an inverted U-shape relationship, implying that optimal temperature and precipitation levels with respect to output do exist, and iii) different assumptions about economic growth and its distribution over regions, as projected by the SSPs, increase the relative share of global GVA for currently rather poor countries with high average temperatures. We find that in global terms, economically efficient levels of SRM are affected more by region-specific economic growth projections than by regional climate-change impacts. Globally, the economically efficient SRM level is proportional to the (global) GVA-weighted mean temperature increase, which varies considerably according to the various growth projections (for equal climatic background conditions). Achieving the optimal temperature in each scenario is constrained by the influence of SRM on precipitation.
Keywords: Q54; O44; 330; Climate engineering; Solar radiation management; Governance; Climate-change winners and losers